Qualidade institucional e compliance público: implicações teóricas e práticas no Tribunal de Justiça do Estado do Maranhão - CÂMARA, David Elias Cardoso (2024)
In recent years, corruption has become prominent in Brazil, driven by scandals that have impacted the political-economic scenario. In response, the country has promoted legislative reforms focused on mitigating risks, emphasizing the importance of the Justice System Institutions, which play a crucial role in public administration, in defending collective interests, and in the proper application of public resources. This investigation focuses on how the Court of Justice of the State of Maranhão (TJMA) developed an integrity program and its effectiveness in light of Resolution N. 410 of 2021 from the National Council of Justice (CNJ), which established a compliance system for all Justice Courts in the country. Adopting an inductive method of qualitative approach, methodologically grounded in a monographic, comparative, and critical socio-juridical analysis, the research concluded that, initially, the TJMA implemented public governance practices in a satisfactory manner and in accordance with the guidelines of the CNJ.